MENGASAH PROFESIONALITAS DOSEN DALAM DUNIA DISRUPTIF - Vinsensius Crispinus Lemba (Jurnal Reinha, 2021)
This article examines the professionalism of lecturers in the disruptive world. The disruptive world is a world full of change and is a character of the Industrial Revolution 4.0. The disruptive world brings together two great forces, namely globalization and technology. Technology in the disruptive world prioritizes automation and digitization with five main pillars that form the basis of the Industrial Revolution 4.0, namely the internet of things, big data, artificial intelligence, cloud computing, and additive manufacturing. The disruptive world demands the ability to adapt to the changes it produces. Universities as world centers of excellence, driven by educated humans to produce superior and competitive human beings are required to be able to face changes in a disruptive world. One of the main components needed in this case, namely professional lecturers. Professional lecturers are not determined only in terms of academic qualifications, but also superior and competitive competencies. The professionalism required of lecturers in a disruptive world, which is also needed in the 21st century world, can be improved by honing three main skills, namely learning and innovation skills, digital literacy skills, and career and life skills. These three skills can produce higher education outputs and outcomes, specifically in the form of graduates who have high competitiveness and are ready to compete in the Industrial Revolution 4.0 era.